Transient fault detection and location in power distribution network: a review of current practices and challenges in Malaysia - Asman, Saidatul Habsah; Ab Aziz, Nur Fadilah; Ungku Amirulddin Al Amin, Ungku Anisa; Ab Kadir, Mohd Zainal Abidin (MDPI, 2021)
An auto-restoration tool to minimize the impact of faults is one of the critical requirements in a power distribution system. A fault-monitoring system is needed for practical remote supervision to identify faults and reduce their impacts, and thus reduce economic losses. An effective fault-monitoring system is beneficial to improve the reliability of a protection system when faults evolve. Therefore, fault monitoring could play an important role in enhancing the safety standards of systems. Among the various fault occurrences, the transient fault is a prominent cause in Malaysia power systems but gains less attention due to its ability of self-clearance, although sometimes it unnecessarily triggers the operation of protection systems. However, the transient fault is an issue that must be addressed based on its effect that can lead to outages and short-circuits if prolonged. In this study, the authors summarize the guidelines and related standards of fault interaction associated with a monitoring system. The necessity of transient fault detection and location techniques and their limitations, the need for signal processing, as well as recommended practices, are also discussed in this paper. Some of the practices from local power utility are also shared, indicating the current approaches, key challenges, and the opportunities for improvement of fault-monitoring systems due to transient fault, which can be correlated with the reviews provided.